La expression y el control de la impulsivida como function de la conducta intectual en niños - Laosa, Luis M. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
In an attempt to understand the relationship, by sex and age, between intellectual performance variables and measures of impulse expression and control, scores on 4 subtests of the Wechsler Intelligence Scales for Children (WISC) and for Adults (WAIS), were compared with performance on 3 Personality Research Form scales—Im- pulsivity (Imp), Harmavoidance (Ha), and Order (Or)— for 297 children of three age groups (11.7, 14.7 and 17.7 years). No significant relationships were found between Imp or Ha and any of the measures of intellectual performance. Significant relationships (— > .01) between Or and WISC and WAIS variables showed that untidy Ss perform better in Vocabulary and Arithmetic than neat and organized Ss.